The use of the combined vector vaccine GamCOVID-Vac (Sputnik V) in patients with immuno-inflammatory rheumatic diseases: safety issues-news - A. N. Kulikov; N. V. Muravyeva; B. S. Belov; S. I. Glukhova (Научно-практическая ревматология)
The aim of the study was to assess the safety of the combined vector vaccine Gam-COVID-Vac (Sputnik V) and to determine the risk factors for the development of adverse events in patients with immuno-inflammatory rheumatic diseases (IIRD). Patients and methods. A single-stage study of patients with IIRD who were on inpatient treatment or who applied to the consultative and diagnostic center of the V.A. Nasonova Research Institute of Rheumatology was conducted, who received both components of the Sputnik V vaccine. The control group included immunized persons without IIRD. All participants were interviewed by a research doctor with filling out a unified questionnaire, additional information was obtained from medical documentation. Results. The study included 325 patients with IIRD and 138 healthy controls. After vaccination with the first component, the number of patients with IIRD, in whom the development of local and systemic adverse events (AEs) was noted, was significantly lower compared to the control (20.3% and 38.4% respectively; p<0.001). These differences also persisted after immunization with the second component (12.3% and 28.3% respectively, p<0.001). After complete vaccination, no AEs were documented in 40.3% of patients and 22.5% of the control group (p<0.001). Female sex and, possibly, methotrexate therapy increases the risk of developing local and systemic AEs on the first component of the vaccine, rituximab therapy - on the second. A lower incidence of AEs is typical for elderly patients, patients with a disease duration of more than 10 years and obesity. Exacerbation of IIRD was registered in 1 (0.3%) case, the occurrence of new autoimmune phenomena was not observed. Conclusions. According to the data obtained, the use of Gam-COVID-Vac (Sputnik V) in patients with IIRD is safe.